2019
DOI: 10.1063/1.5091573
|View full text |Cite
|
Sign up to set email alerts
|

Computational research on film cooling performance of different shaped holes with backward and forward injection

Abstract: The present work has been performed to evaluate the effect of three shaped holes (cylindrical hole, expansion-shaped hole and fan-shaped hole) with forward injection and backward injection on film cooling effectiveness on the adiabatic wall flat plate. All the cases are computed under eight blowing ratios (M) = [0.25, 0.5, 0.75, 1.0, 1.25, 1.5, 1.75 and 2.0]. The results show that for film cooling hole structure with backward injection, a pair of rotating vortex is formed at the outlet of film cooling hole. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Under a low blowing ratio of M = 0.5, the backward injection produces greater η ad,l-av in the immediate downstream region behind the film cooling hole (X/D < 2) but slightly lower η ad,l-av on the far downward film-cooled surface (X/D ≥ 3) than the forward injection. These findings agree well with the previous findings of Zhao et al [37], who suggested that the critical blowing ratio in cylindrical hole film cooling, where backward injection performance surpasses that of the forward injection, is 0.5.…”
Section: Different Roles Of Upstream Ramps On Film Cooling Enhancementsupporting
confidence: 93%
See 1 more Smart Citation
“…Under a low blowing ratio of M = 0.5, the backward injection produces greater η ad,l-av in the immediate downstream region behind the film cooling hole (X/D < 2) but slightly lower η ad,l-av on the far downward film-cooled surface (X/D ≥ 3) than the forward injection. These findings agree well with the previous findings of Zhao et al [37], who suggested that the critical blowing ratio in cylindrical hole film cooling, where backward injection performance surpasses that of the forward injection, is 0.5.…”
Section: Different Roles Of Upstream Ramps On Film Cooling Enhancementsupporting
confidence: 93%
“…Their results demonstrate that the backward-injection scheme greatly improves the film cooling effectiveness for the cylindrical holes at higher blowing ratios, but with a fan-shaped hole, it slightly reduces the film cooling effectiveness relative to the forward-injection scheme. Zhao et al [37] numerically investigated the effect of coolant injection on the adiabatic film cooling effectiveness of different holes (cylindrical hole, expansion-shaped hole, and fan-shaped hole) under a range of blowing ratios from M = 0.25 to M = 2.0. From the computed results, they identified the critical blowing ratios for different film cooling hole shapes, i.e., the blowing ratio above which backward injection yields higher film cooling effectiveness than forward injection.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that film cooling effectiveness obtained with backward holes was much higher than that of forward holes, and the film cooling effectiveness with backward injection was less sensitive to the inclination angle of film cooling hole. Zhao et al [22] numerically investigated the effect of cylindrical hole, expansion-shaped hole and fan-shaped hole with forward and backward injection on film cooling effectiveness. The results showed that the uniformity of film cooling effectiveness obtained by backward hole was higher than that of the hole with forward injection.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [27] reported in their study that the discharge coefficient decreases by the backward injection compared to the forward injection, in particular at high blow ratio (1.0 to 3.0). Zhao et al [28] examined backward injection with a ramp placed upstream of a coolant hole. The coolant flow generated by the upstream ramp and downward vortex by the backward hole can suppress the intensity the kidney vortexes, which leads to improve the film cooling effectiveness laterally.…”
Section: Introductionmentioning
confidence: 99%